Strategi dalam Meningkatkan Sumber Daya Manusia (Santri) di Organisasi Pesantren - Aprliana, Rifdah Auva; Prawarningrum, Shinta Iffah; Rahmadia, Nurul Anisa; Husna, Difa’ul (Lembaga Yasin AlSys, 2024)
Increasing human resources is to answer the challenges of human life in order to realize better change. This change is a process of social, economic and psychological factors that open up opportunities for new patterns to occur through socialization and behavioral patterns. Its manifestations are patterns in human life where humans experience periods of transition. This research aims to find out what strategies kiayai use to improve human resources. The research method used is library research (library research) where the research process is carried out by collecting various literature that collects information and knowledge related to the topic discussed in this research paper. The documents used as research data sources use several scientific literature in the form of books, journals and supporting websites. In its preparation, the author used descriptive analysis. The results of the research in this article are that there are 2 roles of santri, namely the role of santri in the era of disruption and the role of santri in the millennial era. Meanwhile, the strategies used to improve human resource management can be through 4 methods used to improve the quality of human resources including training methods, understudies, job rotation and progress planning, and counseling.